1987
DOI: 10.1007/bf02798429
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunoassay system and bioseparation process based on thermal phase separating polymers

Abstract: Poly-N-isopropylacrylamide (polyNIPAAm), a water-soluble, thermally precipitating synthetic polymer, has been conjugated together with a monoclonal antibody (MAb) and utilized in a novel separation method for an immunoassay. The PolyNIPAAm precipitates out of water above a critical temperature of 31 degres C, enabling a polymer-bound immune complex to be separated from the solution. The principal advantages of this method are that it utilizes a homogeneous incubation for the antigen-antibody reaction, plus, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(106 citation statements)
references
References 3 publications
0
106
0
Order By: Relevance
“…The results showed that the immune reaction would reach equilibrium within 4 min, which is much shorter than that of solid immunoreaction [26], and immuoreactions modulated by temperature-sensitive polymers [6][7][8][9][10].…”
Section: Optimization Of Immunoassay Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the immune reaction would reach equilibrium within 4 min, which is much shorter than that of solid immunoreaction [26], and immuoreactions modulated by temperature-sensitive polymers [6][7][8][9][10].…”
Section: Optimization Of Immunoassay Conditionsmentioning
confidence: 99%
“…Among the temperature-sensitive polymers, poly-N-isopropylacrylamide (PNIP) is known to have a LCST of about 31 • C throughout a wide concentration range. The special thermo-sensitive characteristic of PNIP was successfully exploited in immunoassays by Hoffman et al decades ago [6]. Then PNIP has been widely utilized as the separation carrier in immunoassays [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A stock solution of 5.3 mg/mL FITC-antigen was made by mixing 0.15 mL of 0.36 mg/mL FITC solution with 1.5 mL of 5.3 mg/mL antigen (dissolved in 0.5 M sodium carbonate buffer at pH 9.5) in a 10 mL beaker [3]. The mixture was vortex-mixed and left in the dark at room temperature for 4±6 h before use.…”
Section: Preparation Of Fitc-antigenmentioning
confidence: 99%
“…PNIP precipitates out of water when the temperature is raised above the lower critical solution temperature (LCST, about 31 ), and ℃ re-dissolve when the solution temperature is lowered below the LCST. The special temperature-sensitive characteristic of PNIP was successfully exploited in immunoassays by Hoffman et al 4 decades ago. Afterwards PNIP was widely utilized as the separation carrier in immunoassays.…”
Section: Introductionmentioning
confidence: 99%